(untitled) (REMUNOM, 2025)
This article analyzes the Brazilian Tax Reform with a focus on the Tax on Industrialized Products (IPI) and the Tax on Services of Any Kind (ISS). It explores the historical evolution of these taxes in both international and national contexts, highlighting their similarities with consumption tax models such as the European Value-Added Tax (VAT). The IPI and ISS are presented as federal and municipal taxes, respectively, emphasizing their fiscal and extrafiscal functions, as well as their importance for the financial autonomy of the federative entities. The study details the concepts of tax jurisdiction and tax types, along with the constitutional principles applicable to these taxes. Finally, it examines the collection methods, current rates, and revenue distribution, underscoring the complexity of the Brazilian tax system and the need for reform.